2007
DOI: 10.1021/tx700273u
|View full text |Cite
|
Sign up to set email alerts
|

Chemical–Biological Fingerprinting: Probing the Properties of DNA Lesions Formed by Peroxynitrite

Abstract: DNA-damaging agents usually produce a vast collection of lesions within the genome. Analysis of these lesions from the structural and biological viewpoints is often complicated by the reality that some of the lesions are chemically fragile, leading to an even larger set of secondary and tertiary products. In an effort to deconvolute complex DNA-damage spectra, a strategy is presented whereby an oligonucleotide containing a specific target for chemical reaction is allowed to react with a DNAdamaging agent. A la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 71 publications
2
44
0
Order By: Relevance
“…Lastly, a templating Z lesion when bypassed by a polymerase allows insertion of mainly dATP leading to G→T transversion mutations [161]. Cellular studies using the REAP assay verified the in vitro results in which Z preferentially induces G→T transversions ~95% of the time [159]. Besides OG, the other G-derived lesions are nearly ~100% mutagenic causing G→T or G→C transversion mutations.…”
Section: Products Of G Oxidation Are Mutagenic On the Basis Of Celmentioning
confidence: 98%
See 1 more Smart Citation
“…Lastly, a templating Z lesion when bypassed by a polymerase allows insertion of mainly dATP leading to G→T transversion mutations [161]. Cellular studies using the REAP assay verified the in vitro results in which Z preferentially induces G→T transversions ~95% of the time [159]. Besides OG, the other G-derived lesions are nearly ~100% mutagenic causing G→T or G→C transversion mutations.…”
Section: Products Of G Oxidation Are Mutagenic On the Basis Of Celmentioning
confidence: 98%
“…Studies to inspect Sp and Gh mutational profiles by the REAP assay verified their ability to cause transversion mutations in ~100% yield [156, 159, 160]. The results indicated that the Sp base stereochemistry impacted the ratio of G→T and G→C transversions.…”
Section: Products Of G Oxidation Are Mutagenic On the Basis Of Celmentioning
confidence: 99%
“…In addition to highly labile normal and all oxidized abasic sites [113], this analysis reveals several oxidatively generated base modifications, which are at least partly con-vertedintoSSBs,suchas2,5-diamino-4 H -imidazolone (Iz) [116], 2,2,4-triamino-5-(2 H )-oxazolone (Oz) [117], 5,6-dihydroxy-5,6-dihydrothymine (ThyGly) [118], FapyAde and, to lesser extent, FapyGua [119]. In contrast to previous claims, 8-oxoGua has been found to be stable under conditions of hot piperidine treatment [117,120]. The strongly alkaline conditions (0.3M NaOH, pH > 13) that are used for the measurement of DNA strand breaks using either the alkaline version of the comet assay or the alkaline eluting technique are incompatible with the instability at high pH of abasic sites, Iz and Oz.…”
Section: Classes Of Oxidatively Generated Damagementioning
confidence: 99%
“…27 In vivo studies demonstrated that both hydantoins show 100% mutagenesis causing dG→dT and dG→dC (2′-deoxycytidine) transversion mutations if unrepaired. 2830 These biological observations have implicated the hydantoins as potential culprits for causing mutations that result from oxidative and inflammatory stress leading to disease progression.…”
Section: Introductionmentioning
confidence: 99%